Investigative Journalism in the Arab World - Bebawi, Saba. author. aut Link
XI, 175 p.
Keywords: This is the first book that looks into the state and role of investigate journalism in the Arab world. It explores the vital role the media could potentially play in informing and empowering society, to assist in opening up the communicative space in a region where this has previously been taboo.